A model for assessing the effectiveness of swimming technique in the training of young sprint swimmers - Maryin, I.S.; Gridneva, E.V.; Fetisov, V.N.; Ponimasov, O.E. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop a model of swimming technique based on anthropometric factors, strength, power and the kinematic characteristics of young swimmers. Methods and structure of the study. The study involved 24 young male swimmers aged 12.5±0.9 years, with 3.5 years’ experience in competitive swimming, who regularly participate in regional competitions. A factor model of swimming technique effectiveness has been developed, taking into account current data on the factors determining the performance of young swimmers during the training phase of their preparation. Results and conclusions. The factor model of swimming technique efficiency includes variables relating to total force, hydrodynamic power and the kinematic efficiency of the stroke, which account for 68.7% of the performance of young swimmers.